Stand structure and biomass estimation for cultivation of Agarwood-producing species on Buru Island, Maluku Province, Indonesia - Pratama, Bayu Arief; Atikah, Tika Dewi; Susanti, Ruliyana; Jakalalana, Supardi; Ferdinandus, Stanly P.; Maail, Rohny Setiawan (Media Konservasi, 2025)
Agarwood is a resin product of agarwood-producing species belonging to the Thymelaeaceae family. This product is categorized as a non-timber forest product and has high value. Species of Aquilaria filaria (Oken) Merr. and Aquilaria cumingiana (Decne.) Ridl. are two agarwood-producing species known to grow natively in the Maluku region. This research aims to observe the stand structure and biomass estimation in several Aquilaria sp. cultivation gardens on Buru Island. Five observation plots with sizes 20 x 20 m have been created in three villages on Buru Island. Standard vegetation analysis, principal component analysis, and simulation of aboveground biomass using bootstrap techniques have already been done. Aquilaria sp. is the most important species in the observed community based on the important value index and cos2 value from principal component analysis. The diversity index shows the medium category with mostly stable conditions based on the evenness index. While the biomass estimation shows an average value of 600.50 kg ha-1 with a standard error 273.26 kg ha-1.